Hubungan Sikap Bidan Dalam Menerapkan Standart Operasional Prosedur Kebidanan Pada Tindakan Kegawatdaruratan Obstetri Di RSU Haji Surabaya - Ummah, Kholifatul; Reswari, Putu Ayu Dhana (Jurnal Midpro, 2019)
The most emergent cases of emergencies are bleeding and eclampsia, in emergency cases such as these, actions that require a health worker, especially midwives, act quickly and responsively. Problems then arise when the actions taken have a substantial risk, so that midwives are required to be skilled and master the operational standard of obstetric procedures in handling neonatal maternal emergency cases.One of the data presented is data from the ASEAN Millennium Development Goals (MDGs) in 2017. The data shows that in 2015 maternal mortality in Indonesia still reached 305 per 100 thousand. This figure is three times higher than the MDGs target of Indonesia, which is 102 per 100,000.It was recorded in Surabaya City Health Office that in 2017 the number of neonatal cases handled was 2,785 cases or 67.5% of the total estimated 4,128 neonates, an increase from 2018 the number of neonatal cases handled by 2,187 (56.4%) of the total estimated 3,878 neonates complications. When compared with 2016, the number of high risk pregnant women / complications found in Surabaya was 5,663 people and pregnant women / complications referred were 79.99% indicating a decrease in cases.The method used is cross-sectional sample used purposive sampling, the test used is chi square, from this study it is expected to know the relationship between midwives' attitudes in applying operational standard obstetric procedures in obstetric emergency actions at RSU Haji SurabayaKeywords: Attitude, Standard Operational Procedure